ANALISIS TRANSPARANSI DAN AKUNTABILITAS PADA LEMBAGA AMIL ZAKAT TERHADAP LOYALITAS MUZAKKI - Adama, Muhamad; Burhan, Umar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Analysis of Transparency and Accountability at Amil Zakat Institutions on Muzakki Loyalty (Perception Study at BAZNAS Depok City). This study aims to analyze the influence of each variable, namely the effect of transparency and accountability of Amil Zakat institutions on muzakki loyalty. Lembaga Amil Zakat as a non-profit organization needs to focus on institutional transparency and accountability to increase muzakki loyalty. In this study, data was collected through probability sampling questionnaires. The respondents of this study were muzakki or those who paid their zakat through the Depok City Baznas. The analysis technique used is logistic regression analysis. The results of this study show that two independent variables, namely transparency and accountability, have a positive effect on muzakki loyalty. This means that the higher the transparency and accountability of the institution, the higher the loyalty of the muzakki.